2022
DOI: 10.3390/nano12060926
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Docetaxel Adsorption on Graphene Quantum Dots Surface Modified by PEG-b-PLA Copolymers

Abstract: Cancer is associated with a high level of morbidity and mortality, and has a significant economic burden on health care systems around the world in almost all countries due to poor living and nutritional conditions. In recent years, with the development of nanomaterials, research into the drug delivery system has become a new field of cancer treatment. With increasing interest, much research has been obtained on carbon-based nanomaterials (CBNs); however, their use has been limited, due to their impact on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Yoosefian et al used PEG‐branched polylactide (b‐PLA) copolymer to modify the surface of GQDs to investigate the drug loading of both normal and surface‐modified GQDs for the chemotherapeutic agent docetaxel, utilizing the theoretical method of molecular dynamics. It was reported that the presence of copolymer on the surface of GQDs increased the solubility and adsorption of the drug (Yoosefian et al, 2022). Gong et al prepared fluorinated GQDs and loaded the drug diclofenac sodium, whereby drug loading could be visually monitored.…”
Section: Carbon Quantum Dots In Drug Deliverymentioning
confidence: 99%
“…Yoosefian et al used PEG‐branched polylactide (b‐PLA) copolymer to modify the surface of GQDs to investigate the drug loading of both normal and surface‐modified GQDs for the chemotherapeutic agent docetaxel, utilizing the theoretical method of molecular dynamics. It was reported that the presence of copolymer on the surface of GQDs increased the solubility and adsorption of the drug (Yoosefian et al, 2022). Gong et al prepared fluorinated GQDs and loaded the drug diclofenac sodium, whereby drug loading could be visually monitored.…”
Section: Carbon Quantum Dots In Drug Deliverymentioning
confidence: 99%
“…This system has good stability, and the presence of copolymers delays drug adsorption and increases the adsorption and solubility of DTX. 271 Felix et al used imatinib-modified graphene quantum dots (GQDs@imatinb) for the treatment of leukemia. The properties and morphology of the GQDs did not change after surface loading of the imatinib.…”
Section: Biological Applications Of Quantum Dotsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] On the basis of its ultrahigh surface area, graphene possesses a high loading capacity for the anticancer drugs through p-p stacking and hydrophobic interactions. [22][23][24][25] In this regard, a substantial number of preclinical and clinical studies suggest the suitability of graphene and its derivatives to be used as carriers for anticancer drugs such as doxorubicin, 21,22,25,26 5-fluorouracil (5-FU), [22][23][24][25]27,28 docetaxel, [29][30][31] etc. 5-Fluorouracil is a uracil analogue, with the fluorination of carbon at the fifth position of the pyrimidine heterocyclic ring.…”
Section: Introductionmentioning
confidence: 99%